2019
DOI: 10.1039/c9ra05994f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen exposure on fermentation process and sensory qualities of Sichuan pickle (paocai)

Abstract: The physicochemical and microbial changes, volatile profile, texture and appearance were investigated in three groups of Sichuan pickles differing in oxygen exposure during a 64 day fermentation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
(58 reference statements)
2
10
0
Order By: Relevance
“…This is due to the adding potassium sorbate and sodium D-isoascorbate during the processing of Sichuan sauerkraut after heat treatment. In this series of processing, greatly inhibited the growth of lactic acid bacteria and mold in Sichuan sauerkraut [ 1 , 35 ]. Although the number of microorganisms in Sichuan sauerkraut is very less, it has a certain impact on the quality of sauerkraut.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the adding potassium sorbate and sodium D-isoascorbate during the processing of Sichuan sauerkraut after heat treatment. In this series of processing, greatly inhibited the growth of lactic acid bacteria and mold in Sichuan sauerkraut [ 1 , 35 ]. Although the number of microorganisms in Sichuan sauerkraut is very less, it has a certain impact on the quality of sauerkraut.…”
Section: Resultsmentioning
confidence: 99%
“…Rao et al . (2019) found that the hardness of Sichuan pickle decreased with the extension of the fermentation time whether it was aerobic or anaerobic fermentation, while the pickle without oxygen exposure showed a higher hardness than that with oxygen exposure in the whole fermentation. Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The methodology for counting lactic acid bacteria content is assessed in triplicates using the method of Rao et al (2019) with partial modifications. After diluting with 0.9% saline solution, LAB counts in different groups were determined by enumeration on MRS agar (Tuopu Biol-Engineering Co., Shangdong, China) and incubated at 37 • C for 48 h. Lactic acid bacteria content is expressed as CFU per milliliter.…”
Section: Lactic Acid Bacteria (Lab) Measurementmentioning
confidence: 99%